EFL STUDENTS PERCEPTIONS ON THE ACCESSIBILITY OF E-BOOK: A CASE STUDY IN ENGLISH LANGUAGE EDUCATION PROGRAMME CLASS A 2019 IN MULAWARMAN UNIVERSITY - Audi Risky Ramadhani; Dyah Sunggingwati; Istanti Hermagustiana (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2024)
EFL students often receive assignments via digital platforms, specifically pdfs or e-books, such as article analysis for reading comprehension and EFL students' experience accessing e-book. People' reading preferences and behavior have changed due to the advancement of electronic book (e-book) technology. .This study is intended for 2019 A English Department students at Mulawarman University who have finished the advanced reading course and from these criteria. The researcher selected 7 participants from the questionnaire results, and interview them. Almost all participants felt that there are numerous solutions to challenges associated with the use of electronic books. Some participants claimed they preferred to utilize the e-book's search box to find keywords they were interested in. Other individuals stated that simply looking for what we enjoy might be a motivator to engage in reading. The researcher found that efl students have several reasons for using e-books as their most convenient reading tool.